The Influence of Leadership and Loyalty on Employee Performance PT. Pertamina Patra Niaga - Kalsum, Eka Umi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2024)
This research aims to determine the influence of leadership and loyalty on employee performance at PT. Pertamina Patra Niaga. The population in this study were employees of PT. Pertamina Patra Niaga with a sample size of 85 people. The data analysis model used is multiple linear regression analysis. The research method uses a quantitative descriptive approach supported by surveys, and is explanatory. The results of research using partial testing (t test) show that leadership has a positive and significant effect on the performance of PT employees. Pertamina Patra Niaga. Loyalty has a positive and significant effect on the performance of PT employees. Pertamina Patra Niaga. Furthermore, the results of the simultaneous test (F test) show that leadership and loyalty have a positive and significant effect on the performance of PT employees. Pertamina Patra Niaga. The coefficient of determination (R2) value of job satisfaction and competence is able to explain the performance variable by 50.2% and the remaining 40.8% is influenced by other variables not examined in this research such as compensation, work environment, organizational culture and so on.